2013
DOI: 10.1523/jneurosci.0291-13.2013
|View full text |Cite
|
Sign up to set email alerts
|

Olfactory Functions Scale with Circuit Restoration in a Rapidly Reversible Alzheimer's Disease Model

Abstract: Neural circuits maintain a precise organization that is vital for normal brain functions and behaviors, but become disrupted during neurological disease. Understanding the connection between wiring accuracy and function to measure disease progression or recovery has been difficult because of the complexity of behavioral circuits. The olfactory system maintains well-defined neural connections that regenerate throughout life. We previously established a reversible in vivo model of Alzheimer's disease by overexpr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
40
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(45 citation statements)
references
References 80 publications
5
40
0
Order By: Relevance
“…This hyper-excitability emerged by at least 3 MO and remained through at least 16 MO. These findings mirror other studies that have demonstrated the effect of AβPP metabolites in inducing neurotoxic effects (Bach, et al, 2001, Bertrand, et al, 2001, Cheng, et al, 2013, Cheng, et al, 2011, Devi and Ohno, 2012, Dewachter, et al, 2002, Lu, et al, 2000, McPhie, et al, 2001, Sopher, et al, 1994, Yankner, et al, 1989). However, to the best of our knowledge, this is the first investigation of this disrupted firing activity in the LEC in response to odor stimuli.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This hyper-excitability emerged by at least 3 MO and remained through at least 16 MO. These findings mirror other studies that have demonstrated the effect of AβPP metabolites in inducing neurotoxic effects (Bach, et al, 2001, Bertrand, et al, 2001, Cheng, et al, 2013, Cheng, et al, 2011, Devi and Ohno, 2012, Dewachter, et al, 2002, Lu, et al, 2000, McPhie, et al, 2001, Sopher, et al, 1994, Yankner, et al, 1989). However, to the best of our knowledge, this is the first investigation of this disrupted firing activity in the LEC in response to odor stimuli.…”
Section: Discussionsupporting
confidence: 90%
“…Cleavage by the latter results in a β C-terminal fragment (βCTF) that contains the Aβ domain and generates Aβ and AβPP intracellular cytoplasmic domain when further processed by γ-secretase (Zheng and Koo, 2006, Zheng and Koo, 2011). The human AβPP metabolites Aβ and AβPP-CTF have been shown to exhibit some level of cytotoxicity in the pre-depositing brain, ranging from inducing endosome anomalies and apoptosis (Bertrand, et al, 2001, Cheng, et al, 2013, Deyts, et al, 2012, Jiang, et al, 2010, Kayed, et al, 2003, Lauritzen, et al, 2012, Lu, et al, 2000, McPhie, et al, 2001, Nhan, et al, 2014, Tamayev and D’Adamio, 2012, Tamayev, et al, 2012, Upadhaya, et al, 2012) to causing abnormal rewiring of neurons (Cheng, et al, 2011) and functional disruption of synapses (Lacor, et al, 2004). …”
Section: Introductionmentioning
confidence: 99%
“…21 Caspase-3 is the predominant effector Caspase in mammalian tissues and caspase-3 activation induces caspase-3-activated DNase activity. This process causes apoptosis, karyorrhexis, shrinkage, and degradation of DNA.…”
Section: Discussionmentioning
confidence: 99%
“…From a broader perspective, the study of olfaction sits at the intersection of many vibrant disciplines, including neuroscience, genetics, and immunology [77,78]. For the AD field, animal model studies, some employing highly innovative techniques [79], are yielding important insights; neurogenesis within the olfactory structures holds treatment potential [80]; the possibility that biopsy of olfactory mucosa might aid early diagnosis is again under discussion [2•, 34]. As a window on the brain and disease, the olfactory system richly rewards study.…”
Section: Discussionmentioning
confidence: 99%